Serum Specific Antibodies Do Not Seem to Have an Additional Role in the Diagnosis of Hypersensitivity Pneumonitis - Demirkol, Baris; Satici, Celal; Tanriverdi, Elif; Eren, Ramazan; Altundas Hatman, Elif; Yardimci, Hande Aytul; Urer, Halide Nur; Baydili, Kursad Nuri; Cetinkaya, Erdogan (La Medicina del Lavoro, 2023)
Background: We aimed to investigate the contribution of serum IgG testing to the history of exposure in the diagnosis of fibrotic hypersensitivity pneumonitis. Methods: A single-center, retrospective, cross-sectional study including 63 patients pathologically diagnosed with fibrotic hypersensitivity pneumonitis in line with the guidelines of the American Thoracic Society. Descriptive statistics were presented and Kappa statistic was performed to evaluate the compatibility between panel and the history of exposure. Results: The median age was 63 (22-81) years and 34 (54%) were male. Forty-six patients (73%) had a positive history of exposure. Thirty-nine patients (61.9%) had a positive HP/Avian panel. The most common exposure agent was mold (34.9%), followed by parakeet (31.7%). The antibody detected the most was penicillium chrysogenum lgG (36.5%), followed by aspergillus fumigatus (31.8%). There was no compatibility between HP/Avian panel and history of exposure (kappa coefficient= 0.18, p= 0.14). When the exposure was only assessed based on the history, 4 (6.35%) patients were diagnosed as fibrotic hypersensitivity pneumonitis with low confidence, 6 (9.52%) with moderate confidence, 11 (17.46%) with high confidence and 42 (66.67%) with definite confidence; whereas 4 (6.35%) patients were diagnosed as fibrotic hypersensitivity pneumonitis with low confidence, 6 (9.52%) with moderate confidence, 9 (14.29%) patients with high confidence and 44 (69.84%) patients with definite confidence if exposure was evaluated with history and/or panel. Conclusions: Serum specific precipitating antibody panel does not seem to provide additional value to the history of exposure in the diagnosis of fibrotic hypersensitivity pneumonitis.